Long-term patient reported sexual and urological dysfunction in males after operatively treated pelvic ring injuries Do generic outcome measures identify genitourinary health problems?. Issue 6 (June 2022) - Bott, Alasdair; Nicol, Graeme; Odutola, Adekoyejo; Halliday, Ruth; Acharya, Mehool R.; Ward, Anthony; Chesser, Timothy J.S.
Highlights: Urological and sexual dysfunction must be separately recorded to understand the global functional outcome of patients following a pelvic injury. Patients without genitourinary injury experience sexual and urological dysfunction after pelvic fracture. 37% of male patients report severe sexual dysfunction after pelvic fracture. Long-term sexual and/or urological dysfunction is not identifiable on EQ-5D-3L and other outcome scores used in assessment of pelvic ring injury. Abstract: Background: A consecutive series of 177 male patients, with high energy pelvic ring injuries, were treated operatively in our institution. The purpose of this study was to evaluate long-term sexual and urological dysfunction in these patients using validated disease specific patient reported outcome measures (PROMs), and identify if sexual and urological dysfunction is detectable from generic outcome scores used in the assessment of pelvic ring injury at a minimum of 10 years follow-up (range 10–22). Methods: Surviving patients were contacted to complete validated PROMs to examine genitourinary and global functional outcome. Fifty-two male participants, had a mean age of 44-years-old (range, 16–69) and ISS of 17 at time of injury. Mean duration follow-up of 15 years. The primary outcome measures were the Sexual Health Inventory for Men (SHIM) and the Modular Questionnaire for Male Lower Urinary Tract Symptoms (MLUTS). Secondary outcomes were the EQ-5D and Short Form 36. Responses were tested for correlation between generic and disease-specific PROMs and analyzed for association with genitourinary injury and age as risk factors of poor outcome. Results: Genitourinary injuries occurred in 7 patients (13%), and ten patients (19%) had documented neurological dysfunction following injury. Satisfactory general functional outcome was reported with EQ-5D-3L VAS score of 71. However, 80% report some level of sexual dysfunction with 37% reporting it as severe. MLUTS mean symptom score was 9 (range, 0 – 26) and bothersomeness score was 21 (range, 0–90). There was poor correlation between urological and sexual dysfunction scores and between the disease specific and generic scores. Conclusion: In operatively treated pelvic ring injuries, validated disease specific PROMs, (SHIM and MLUTs) identified a significant impact to both sexual and urological patient health, with 37% reporting severe sexual dysfunction. Longstanding sexual and/or urological dysfunction can be a source of significant psychological impact that this study has shown is not identifiable using generic PROMs; EQ-5D-3L and SF-36. To gain a holistic understanding of the functional outcome of patients following a pelvic injury, urological and sexual dysfunction must not be overlooked.